Multifunction dynamic model of structural fractal of complex technical system - Павлов, В.В.; Чепиженко, В.И. (Proceedings of National Aviation University, 2010)
On the basis of system conception of evolution dynamic processes research of the complex, functionally integral technical systems technical state on all of interval of their life cycle the multifunction dynamic model of structural fractal of the complex technical system is developed. Information and power levels association in the offered model allows integrately to model the dynamic processes of system purpose functioning, changing evolutional processes of its state, structural changes in the system in the exploitation process, and also dynamic processes of the system cost changing on all of operating interval of its life cycle. The offered model is foundation for the synthesis of control the dynamic processes of purpose functioning of the complex multidimensional systems, for their structural and functional states, and also control cost and power processes.